Nutritional quality of cultured Asian seabass Lates calcarifer in Khulna-Satkhira region of Bangladesh: comparative analysis of two size classes: Nutritional quality of cultured Asian seabass in Khulna-Satkhira region of Bangladesh - Sikder, Roni; Haque, Wahida; Das, Saikat; Shaon, Md Akeruzzaman; Islam, Md Zafrul; Hasan, Md Rakibul (Dhaka University Journal of Biological Sciences, 2026)
Asian seabass (Lates calcarifer), locally known as Bhetki or Koral, is a native species to the Indo-Pacific region and is farmed on a small scale in the Southern coastal regions of Bangladesh. This study analyzed the nutritional composition of cultured Asian seabass to identify the nutritionally superior size to aid consumers in making informed choices and to help farmers in determining optimal culture duration. Individuals of two different size classes, (512.06 ± 14.5 g and 1003.5 ± 36.64 g) collected from Khulna and Satkhira districts, were analyzed during this study. The results revealed significant differences (p < 0.05) between the two groups in their proximate composition except for ash content. The smaller size group had higher moisture content (74.96 ± 0.04%), while the larger group showed higher protein (20.48 ± 0.1%) and fat (5.34 ± 0.18%) content. Fatty acid profiles also indicated variation between the two groups with larger fish containing higher levels of saturated (SFAs) and monounsaturated fatty acids (MUFAs) whereas smaller fish had more polyunsaturated fatty acids (PUFAs) and a more favorable n-3/n-6 ratio. Undecanoic acid and α-linolenic acid were predominant in both groups, while MUFA composition varied: palmitoleic acid and oleic acid were higher in the smaller and larger groups respectively. All essential amino acids (EAAs) were present except tryptophan. Lysine was the most prominent in both groups with 5.53 ± 0.44 g/100 g dry weight and 3.91 ± 0.32 g/100 g dry weight in the smaller and larger group, respectively. These findings suggest that smaller seabass offer superior nutritional quality and may support more profitable farming through shorter culture cycles. Dhaka Univ. J. Biol. Sci. 35(1): 107-117, 2026 (January)